EXECUTIVE IMPLEMENTATION BY DEBT COLLECTOR AGAINST FIDUSIAN OBJECT GUARANTEE - Martam, Nurmin K (DiH: Jurnal Ilmu Hukum, 2019)
Multi - finance institutions in Indonesia are better if the indicator is the number of consumer finance in Indonesia in the last few years. The growth of consumer financing can be seen from all the convenience given by the multi finance. The factor that dominates the forced withdrawal of Fiduciary Guarantee is the existence of problem loans. This problem is al most certainly experienced by any consumer financing institution. The problems discussed in this research are about how the implementation of execution of fiduciary guarantee in the settlement credit toward four wheels (car) The formulation of problems related to with the withdrawal of vehicles accompanied by violence that is: How about the collection of arrangement or confiscation of a motor vehicle that carried out by debt collector against a debtor non-performing loans, Do factors for the act of violence carried out by debt collector, How a settlement effort the act of violence carried out by debt collector in terms of the aspect of criminal law. This research is classified as the kind of research juridical normative , study legislation as criminal code and civil law, Regulation president of the Republic Indonesia No. 9 of 2009 about Funding Institution, the act of No. 42 of 1999 about Fiduciary Security, Minister of Finance Regulation No. 130/PMK.010/2012 about Registration Fiduciary for Financing Company, this research also is study case that is focus self intensively on an object particular and learn that as a case. Arrangement about the collection of vehicles stipulated in a financing with fiduciary security contained in the act of fiduciary security number 42 of 1999 And also minister of finance regulation No 130/PMK. 010/2012